Albergue para niños y adolescentes en estado de abandono en San Juan de Lurigancho - Asmat Salvatierra, Jose Francisco (2023)
Currently, the state of abandonment that a child in Peru experiences on a daily basis is a matter of vital importance, as every year the numbers of violence, child trafficking, orphan hood, and abandonment increase and focus on a group of vulnerable people who are the foundation and future of society. Unfortunately, child abandonment mostly occurs within the family environment, causing multiple problems in their present and future, and even replicating into adulthood. For this reason, it is proposed to design a preliminary project for a children's shelter in the district of San Juan de Lurigancho based on the model of SOS Children's Villages, with the purpose of providing housing for abandoned children, creating spaces for social and family interaction, and thus improving their quality of life, as well as their cognitive and social development. Furthermore, this research studies the history and evolution of the infrastructure of centers dedicated to the protection of children over time. Some theories, concepts with architectural and psychological approaches, as well as some references, were analyzed in order to understand the user and use them as design and project placement tools, taking into account the corresponding Peruvian regulations. In this project, we embody the idea of a child's development through a family, providing them with a place where they can feel safe, protected, and able to develop their creativity and interact with other children through collective play. Our proposal seeks simplicity through modest architecture, respecting the scale of the child, with sustainability criteria, and above all, with a design focused on minors who have experienced abandonment at some point in their lives.